Synthesis and Microbiological Activity of Some Newly Condensed Derivatives of 2-Oxo-2H-chromen-2-one - Daci-Ajvazi, Majlinda; Govori, Sevdije (Asian Journal of Chemistry, 2013)
By the action of 2-amino-5-ethylthio-1,3,4-thidiazole, 3-amino-5-methyl isoxazole and 2-amino benzimidazole on 4-hydroxy-2-oxo-2H-chromene-3-sulfonyl chloride, corresponding 4-hydroxy-2-oxo-2H-chromene-3-sulfonic acid (5-ethyl-[1,3,4]thiadiazol-2-yl)-amide, 4-hydroxy-2-oxo-2H-chromene-3-sulfonic acid (5-methyl-isoxazol-3-yl)-amide and 4-hydroxy-2-oxo-2H-chromene-3-sulfonic acid (1H-benzimidazol-2-yl)-amide were formed and they have been isolated in satisfying yields. Based on the biological activity of chromene-2-ones and heterocyclic compounds condensed in position 3 and 4, we also studied microbiological activity of these new compounds (4-6), against Staphylococcus aureus ATCC 25923, Streptococcus pneumoniae, Aeromonas salmonicida, Bacillus spp and some of them exhibited significant activity.